PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEMAMPUAN MENULIS MAHASISWA PROGRAM STUDI BAHASA INGGRIS FKIP UNIVERSITAS RIAU - Hadriana, Hadriana (Universitas Muhammadiyah Surakarta, 2012)
This Research is aimed at finding out the level of writing ability of the students atÂ English Study Program FKIP- UNRI by using Cooperative Learning Method. The samples of theÂ research were all of the first year students that joined Writing IC. The procedure of the researchÂ were administered through (a) pre-tes; (b) teaching and learning process by using CooperativeÂ Learning Method; and (c) pos-tes. Pre-tes and pos-tes were given in order to know the level ofÂ their writing ability. Data analysis was conducted by comparing the scores of pre-tes and post-tes.Â Data calculation concluded that with df = 78 â 1 = 77, it was found that r table with significantÂ level 5% = 2.64; and 1% = 1.99 which were smaller than tÂ = 3.005. As a result, null hypothesisÂ (Ho) was rejected and alternative hypothesis (Ha) was accepted. In conclusion, CooperativeÂ Learning Method played a significant role in increasing the writing ability of students of EnglishÂ Study Program FKIP UNRI.